2021
DOI: 10.1111/jfpp.15609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoemulsified canola oil combined with Bakhtiari savory ( Satureja bachtiarica ) essential oil on the quality of chicken breast during refrigerated storage

Abstract: Chicken meat has high nutritive value and widely consumed over the world. It contains high-quality proteins, some minerals and vitamins, polyunsaturated fatty acids, and several bioactive compounds, which are beneficial for human health (Barbut, 2002;Karakök et al., 2010). However, the shelf life of fresh chicken is limited as a result of its susceptibility to spoilage (Barbut, 2002). Therefore, efficient storage technologies are needed to improve its shelf life in fresh state without unfavorable impacts on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
(68 reference statements)
0
5
1
Order By: Relevance
“…Although a decrease in microbial populations has been observed in the present and previous studies, it has also been reported that refrigerated chicken meat treated with nano-emulsions of Satureja bachtiarica EO (2%) did not decrease TPC, EN and LAB by greater than 1 log cfu/g after 8 d storage at refrigeration temperatures ( Pirastehfard et al, 2021 ). A similar observation was seen with cinnamon EO chicken marinated for 6 d where no decreases in TPC, PS, EN, LAB and YM by more than 1 log cfu/g were observed ( Raeisi et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 49%
“…Although a decrease in microbial populations has been observed in the present and previous studies, it has also been reported that refrigerated chicken meat treated with nano-emulsions of Satureja bachtiarica EO (2%) did not decrease TPC, EN and LAB by greater than 1 log cfu/g after 8 d storage at refrigeration temperatures ( Pirastehfard et al, 2021 ). A similar observation was seen with cinnamon EO chicken marinated for 6 d where no decreases in TPC, PS, EN, LAB and YM by more than 1 log cfu/g were observed ( Raeisi et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 49%
“…T4 attempted ( P > 0.05) to reduce abdominal fat by 13.33% compared to controls. High dietary energy EOs are improved carcass traits ( Ghanima et al, 2021 ; Pirastehfard et al, 2021 ). Dietary nano-thyme oil was not affected the carcass traits of broiler chicken ( Yaseen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid oxidation is one of the main causes of meat deterioration, which affects nutritional value and production of unpleasant taste and offodor the taste of meat. The TBARS test evaluates the aldehydes content as the secondary products of lipid oxidation (Pirastehfard et al, 2021). The result of the TBARS analysis of meatballs was presented in (Hasani-Javanmardi et al, 2021).…”
Section: Lipid Oxidationmentioning
confidence: 99%